Analysis of the Role of Regulations for the Protection of Intellectual Property Rights and Technological Innovation on the Protection of Creativity in the Television Industry in Indonesia - Nasution, Emmi Rahmiwita; Mokodenseho, Sabil; Manoppo, Sinta; Paputungan, Siti Nisroha; Mokodompit, Nurcahyani (West Science Interdisciplinary Studies, 2024)
The Indonesian television industry is undergoing significant transformation fueled by technological innovation and evolving regulatory frameworks surrounding intellectual property rights (IPR) protection. This research investigates the regulatory role of IPR protection and technological innovation on creativity within the Indonesian television sector through quantitative analysis. A sample of 150 stakeholders representing various industry segments participated in the study. Descriptive statistics, correlation analysis, and regression analysis were employed to examine the relationships between IPR protection, technological innovation, and creativity. The findings reveal positive correlations between IPR protection, technological innovation, and creativity, with stronger IPR protection and greater technological innovation associated with higher levels of creativity. Regression analysis further demonstrates the predictive power of IPR protection and technological innovation on creative output within the industry. These results underscore the importance of supportive regulatory environments and technological advancement in fostering creativity and innovation within the Indonesian television industry.